2018
DOI: 10.3390/met8070535
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth Rate on the Microstructure and Tensile Behaviour of Directionally Solidified Ti-44Al-9Nb-1Cr-0.2W-0.2Y Alloys

Abstract: Ti-44Al-9Nb-1Cr-0.2W-0.2Y alloys were directionally solidified (DS) at different growth rates varying from 10 to 20 µm/s using a modified liquid metal cooling (LMC) method. The results show that an increase in the growth rate leads to both a decrease in the size of the columnar grains in the directional solidification stable growth zone and a deterioration of the preferred orientation of the α 2 (Ti 3 Al)/γ(TiAl) lamellar structure in the columnar grains. The growth direction of the primary dendrite in the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…When the growth rate varies greatly, it is easy to undergo a change in solidification mode on most occasions. Jiang et al [ 45 ] found that for Ti-44Al-9Nb-1Cr-0.2W-0.2Y alloy, within the range of growth rate of 10~20 μm/s, as the growth rate increased, the angles between the columnar grain orientation and the ingot axial direction gradually decreased, and the preferred grain orientation gradually changed from the heat flow direction to the pulling direction. Moreover, the difference in growth rate caused changes in the primary solidification phase.…”
Section: Controlling Solidification Parametersmentioning
confidence: 99%
“…When the growth rate varies greatly, it is easy to undergo a change in solidification mode on most occasions. Jiang et al [ 45 ] found that for Ti-44Al-9Nb-1Cr-0.2W-0.2Y alloy, within the range of growth rate of 10~20 μm/s, as the growth rate increased, the angles between the columnar grain orientation and the ingot axial direction gradually decreased, and the preferred grain orientation gradually changed from the heat flow direction to the pulling direction. Moreover, the difference in growth rate caused changes in the primary solidification phase.…”
Section: Controlling Solidification Parametersmentioning
confidence: 99%
“…The SPD treatment used to obtain UFG titanium and its alloys, as well as the microstructure and physical and mechanical properties of these materials have been thoroughly studied [3]; however, research continues [5]. The mechanisms of plastic deformation and the fracture of titanium alloys under various combinations and profiles of thermal and mechanical stresses are being studied [6][7][8].…”
Section: Introductionmentioning
confidence: 99%